ANALISIS PENERAPAN SISTEM INFORMASI AKUNTANSI PEMBELIAN SUKU CADANG PADA PT. HASJRAT ABADI SUDIRMAN MANADO - Permata, Dana Nastari; Lambey, Linda; Tangkuman, Steven (JURNAL RISET AKUNTANSI GOING CONCERN, 2017)
Accounting Information System is a Facility that uses technology designed in presenting the data of a companys information to be considered in a decisions on the companys management activities. The purpose of this study is to determine the application of Accounting Information System in spare parts at PT. Hasjrat Abadi Sudirman Manado by comparing between the theory put forward by the experts with the implementation of the company. The analytical method used is descriptive to look systematically about the spatial flow plot and spare parts purchase invoice. The results of research indicate that accounting information system conducted by PT. Hasjrat Abadi Sudirman Manado has been running well enough. The existence of separation of duties and authority according to work responsibilities of each part related to spare parts purchasing system. PT. Hasjrat Abadi Sudirman Manado has been using computerized system to perform a more effective and efficient repair process. This is not so good in terms of the effectiveness of a purchasing accounting information system.Keywords: Accounting Information System, Purchase, Inventory